Outcome of post caesarean pregnancy in a tertiary care centre in south India - Sathya Prabha; Manasi Naralkar; Prema (New Indian Journal of OBGYN, 2020)
Objectives: The objective is to estimate the success rate, safety and efficacy of VBAC (vaginal birth after cesarean section) by comparing the maternal and perinatal outcome with the elective repeat cesarean section (ERCS). Methodology: This was a prospective, cohort study done over a period of twelve months in a tertiary care centre. Based on the patients' preference, a total of 211 women who satisfied the inclusion criteria were divided into two groups - either a trial of labour after cesarean section (TOLAC) or ERCS group. Results: Success rate of VBAC was found to be 47.9%. About 15% of failed VBAC was due to the tendency to abandon a TOLAC midway. Although the maternal complications were found to be higher in TOLAC, p value (0.347) was not found to be significant. There was no increased risk of neonatal morbidity and mortality in the TOLAC group when compared to ERCS (p=0.814). There was also no difference found in APGAR scores (<7) at 5 minutes and NICU admissions in the TOLAC group and in ERCS group (p=0.899). Conclusion: The success rate of VBAC was found to be 47.9%. There was no significant risk of maternal and perinatal complications compared to ERCS.